Dynamic RNA Modifications in Posttranscriptional Regulation - Wang, Xiao (Mol Cell, 2014)
Cellular RNAs can be chemically modified over a hundred different ways. These modifications were once thought to be static, discrete, and utilized to fine-tune RNA structure and function. However, recent studies have revealed that some modifications, like mRNA methylation, can be reversed, and these reversible modifications may play active roles in regulating diverse biological processes. In this perspective, we summarize examples of dynamic RNA modifications that affect biological functions. We further propose that reversible modifications might occur on tRNA, rRNA, and other noncoding RNAs to regulate gene expression analogous to the reversible mRNA methylation.